Sex-related differences in risk factors, type of treatment received and outcomes in patients with atrial fibrillation and acute stroke: Results from the RAF-study (Early Recurrence and Cerebral Bleeding in Patients with Acute Ischemic Stroke and Atrial Fibrillation) - Antonenko, Kateryna; Paciaroni, Maurizio; Agnelli, Giancarlo; Falocci, Nicola; Becattini, Cecilia; Marcheselli, Simona; Rueckert, Christina; Pezzini, Alessandro; Poli, Loris; Padovani, Alessandro; Csiba, Laszló; Szabó, Lilla; et al. (European stroke journal, 2017)
INTRODUCTION: Atrial fibrillation is an independent risk factor of thromboembolism. Women with atrial fibrillation are at a higher overall risk for stroke compared to men with atrial fibrillation. The aim of this study was to evaluate for sex differences in patients with acute stroke and atrial fibrillation, regarding risk factors, treatments received and outcomes. METHODS: Data were analyzed from the "Recurrence and Cerebral Bleeding in Patients with Acute Ischemic Stroke and Atrial Fibrillation" (RAF-study), a prospective, multicenter, international study including only patients with acute stroke and atrial fibrillation. Patients were followed up for 90 days. Disability was measured by the modified Rankin Scale (0-2 favorable outcome, 3-6 unfavorable outcome). RESULTS: Of the 1029 patients enrolled, 561 were women (54.5%) (p < 0.001) and younger (p < 0.001) compared to men. In patients with known atrial fibrillation, women were less likely to receive oral anticoagulants before index stroke (p = 0.026) and were less likely to receive anticoagulants after stroke (71.3% versus 78.4%, p = 0.01). There was no observed sex difference regarding the time of starting anticoagulant therapy between the two groups (6.4 ± 11.7 days for men versus 6.5 ± 12.4 days for women, p = 0.902). Men presented with more severe strokes at onset (mean NIHSS 9.2 ± 6.9 versus 8.1 ± 7.5, p < 0.001). Within 90 days, 46 (8.2%) recurrent ischemic events (stroke/TIA/systemic embolism) and 19 (3.4%) symptomatic cerebral bleedings were found in women compared to 30 (6.4%) and 18 (3.8%) in men (p = 0.28 and p = 0.74). At 90 days, 57.7% of women were disabled or deceased, compared to 41.1% of the men (p < 0.001). Multivariate analysis did not confirm this significance. CONCLUSIONS: Women with atrial fibrillation were less likely to receive oral anticoagulants prior to and after stroke compared to men with atrial fibrillation, and when stroke occurred, regardless of the fact that in our study women were younger and with less severe stroke, outcomes did not differ between the sexes.
Keywords: ischemic stroke; stroke outcome; secondary prevention; Sex differences; atrial fibrillation; anticoagulation therapy